ORGANIZACIÓN CRÍTICA DEL CONOCIMIENTO EN SISTEMAS DE INFORMACIÓN DE MEDIOS (Estudos críticos em organização do conhecimento, 2024)
This research focuses on the presence of subjectivity in the core tasks of massmedia knowledge organizers (MKOS) dealing with press, radio and TV records, suchas classification, representation, and any other process related to content analysis andorganization in News information systems. Far from rejecting subjectivity and ideologicalbias in these operations - since they coparticipate in the media construction of reality—the authors consider MKOS to be genuine ideological and cultural mediators with theright and social responsibility to explicitly state the results of their “objectifiable” work(obtained through KO protocols and procedures determined by the media/company,classifications, thesauri, ontologies, etc.) and differentiate them from those of theirpolitical, ideological, cultural and, in sum, subjective stances. In order to achieve this,we propose the application of critical operators that should be followed by technical,collaborative and even technological actions geared to investing information systems withthe capacity to consider those stances and allowing users to distinguish them. In short, itis the theoretical recognition of the subjective and biased presence of media knowledgeorganization operators in a job that is usually considered neutral, banal and even objective,and the initial development of tools for critical, self-critical, technical, and technologicaltraining keyed to its practical solution. This paper outlines the lines of work of a broaderresearch study on the critical function of KO in the field of global media memory.